Primary health care nurses’ knowledge, self-efficacy and performance of diabetes self-management support in the OR Tambo District, Eastern Cape - Landu, Zandile K. (Stellenbosch : Stellenbosch University, 2022)
Thesis (MNur)--Stellenbosch University, 2022.